Influence of irrigation and nutrition under ultra-high density planting of mango (Mangifera indica L.) cv. 'Alphonso' - Anand M.; Kayalvizhi K.; Sankari A.; Karthi K.; Velmurugan M.; Prabhadharshini M. K.; Nanthakumar S.; Pugalendhi L. (Folia Horticulturae)
The study was conducted to evaluate the irrigation regimes through drip and fertigation levels in ultra-high density planting (UHDP) of mango cv. 'Alphonso'. Three main irrigation regimes, namely, 75% Pan evaporation (I1), 100% Pan evaporation (I2) and 125% Pan evaporation (I3), and four fertigation levels in sub-plots, namely, 50% fertiliser recommended for mango (F1), 75% fertiliser recommended for mango (F2), 100% fertiliser recommended for mango (F3) and 125% fertiliser recommended for mango (F4) were evaluated. Twelve treatments were replicated three times in split plot design. Maximum number of fruits per tree, mean weight of fruit, length of mango fruit, highest tree yield and estimated yield per hectare were recorded in the I2F4 (100% Pan evaporation water per day per plant along with 125% fertiliser recommended for mango by fertigation) treatment. From this study, it could be inferred that in irrigation at 100% Pan evaporation 125% fertiliser for mango by fertigation (I2F4) in UHDP for mango cv. 'Alphonso' were found to be optimum for improving the productivity of the crop with high water and efficiency in fertiliser use.